2022
DOI: 10.2196/38641
|View full text |Cite
|
Sign up to set email alerts
|

Interactivity, Quality, and Content of Websites Promoting Health Behaviors During Infancy: 6-Year Update of the Systematic Assessment

Abstract: Background As of 2021, 89% of the Australian population are active internet users. Although the internet is widely used, there are concerns about the quality, accuracy, and credibility of health-related websites. A 2015 systematic assessment of infant feeding websites and apps available in Australia found that 61% of websites were of poor quality and readability, with minimal coverage of infant feeding topics and lack of author credibility. Objective We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…With websites being a popular source of information about infant and child feeding, it is important that the information available to parents reflects best practices. A 2022 review of websites providing information about health behaviours during infancy, found that the overall scope and depth of the information provided was generally poor, with the majority of websites not catering for users with lower literacy levels and not providing culturally appropriate information for their intended audiences (Jawad et al, 2022 ). Given that many mothers report seeking infant and child feeding information online, this points to opportunities to improve the quality of the information available to parents in this format.…”
Section: Discussionmentioning
confidence: 99%
“…With websites being a popular source of information about infant and child feeding, it is important that the information available to parents reflects best practices. A 2022 review of websites providing information about health behaviours during infancy, found that the overall scope and depth of the information provided was generally poor, with the majority of websites not catering for users with lower literacy levels and not providing culturally appropriate information for their intended audiences (Jawad et al, 2022 ). Given that many mothers report seeking infant and child feeding information online, this points to opportunities to improve the quality of the information available to parents in this format.…”
Section: Discussionmentioning
confidence: 99%
“… 14 , 15 In a 2022 systematic evaluation of 66 infant health websites globally, it was found that the majority of the websites had a high readability level and lacked multilingual options or culturally relevant content. 16 Other studies have shown the impact of immigration on parental health decision-making, and the struggles encountered in navigating between two cultures and reconciling different health practices. 17 , 18 Mothers’ cultural values and customs (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Although some efforts have been made to understand the barriers migrant parents face when accessing health services and resources, 12 16 there is a lack of consolidated information about how migrant parents navigate these challenges and what resources they rely upon. This study aimed to gain further understanding of the barriers and enablers to accessing child health resources and services among migrant mothers in Australia.…”
Section: Introductionmentioning
confidence: 99%
“…Caregivers seeking health information for their children have reported using the internet as their main source of information and reported high levels of confidence [ 25 ], and individuals seeking health information will most often use mobile devices [ 26 ]. However, a review of websites on infant health promotion including infant feeding found that the quality, accessibility and readability of the information was poor or adequate [ 27 ], highlighting the need for the development of interventions for caregivers and HCPs to be evidence-based, appropriate and useable.…”
Section: Introductionmentioning
confidence: 99%